From
( x + y ) 3 = x 3 + 3 x 2 y + 3 x y 2 + y 3
we see that a two-term polynomial that is cubed has four terms in its expansion.
Find the number of terms of a polynomial that when cubed has 100 times more terms in its expansion.
(Assume each term in the polynomial being cubed doesn't share any variables.)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! I added a note to say the cubed polynomial doesn't share any variables, although that might make a good follow-up question!
"However, this only works when the terms of the cubed polynomial don't share any variables."
Well, it might work even if the terms share variables. As long as it's impossible to combine terms. ( x 1 0 + x 3 + 1 ) 3 would expand fully to a polynomial with 1 0 terms, for example.
For n ≥ 3 The only possible different terms of the cubed polynomial are a 3 , a b 2 , and a b c , where a , b , and c are distinct terms of the polynomial x 1 , x 2 , x 3 , ⋯ x n . For n -term polynomial:
Therefore, the number of distinct terms in the cubed n -term polynomial is:
N = N a 3 + N a 2 b + N a b c = n + 2 ( 2 n ) + ( 3 n ) = n + 2 ( 2 n ( n − 1 ) ) + 6 n ( n − 1 ) ( n − 2 ) = n ( 1 + ( n − 1 ) ( 1 + 6 n − 2 ) ) = 6 n ( n + 1 ) ( n + 2 )
For N = 1 0 0 n , then:
6 n ( n + 1 ) ( n + 2 ) ( n + 1 ) ( n + 2 ) ⟹ n = 1 0 0 n = 6 0 0 = ⌊ 6 0 0 ⌋ ⌈ 6 0 0 ⌉ = 2 4 × 2 5 = 2 3
Nice solution!
Why is that the formula for the number of terms of the cube of a polynomial?
Log in to reply
Thanks for asking. I have derived the formula and revised the solution.
Problem Loading...
Note Loading...
Set Loading...
Consider the expansion of ( x 1 + x 2 + … + x n ) 3 . There are terms of the form x i 3 , terms of the form 3 x i 2 x j (with i = j ) and terms of the form 6 x i x j x k ( i , j , k distinct). Respectively, there are n , n ( n − 1 ) , 6 1 n ( n − 1 ) ( n − 2 ) of these terms; so we need to solve
1 0 0 n = n + n ( n − 1 ) + 6 1 n ( n − 1 ) ( n − 2 )
This simplifies to n 2 + 3 n − 5 9 8 = 0 , which has the unique positive root n = 2 3 .
However, this is only guaranteed to work when the terms of the cubed polynomial don't share any variables. For instance, ( x + y + z ) 3 has 1 0 terms in its expanded form, but ( x 2 + x + 1 ) 3 only has 7 . I'm not sure if this means there's another solution.